Review of transportation modes in Kazakhstan region, Central Asia. Issue 1 (1st January 2018) - Bazarbekova, Madina; Assipova, Zhanna; Molgazhdarov, Amangeldy; Yessenov, Meirzhan
Abstract: After the dissolution of the Soviet Union, the former Soviet countries emerged and became independent and began the transition from centrally—planned economy to a market economy. This paper presents a case study of Kazakhstan. This paper aims to review of the transport sector in the Kazakhstan aims to assess the current condition and performance of transport systems and to identify key issues and underlying causes. The paper principally covers development of transportation, condition of current situation, including institutional arrangements, legal and regulatory issues, operation of public transport systems, traffic management, and parking, and less extensively hardware aspects, such as construction of road network. Kazakhstan is located in the heart of Eurasia and plays key role in the logistics between Asia and Europe, in so called "Modern Silk Road". Statistics, analytical materials and legislative frameworks were translated from the references that are in Kazakh and Russian language into English and it brings value to this manuscript. This paper creates different prospectives for future research of transportation modes and infrastructure in Kazakhstan region and central Asia. The research was undertaken to assist researchers and transportation planners to define and comprehend the basic views of transportation.